Results from London Regional Clinical Genetics services over a 5-year period on germline TP53 testing in women diagnosed with breast cancer at <30 years. Issue 6 (15th July 2021) - Garrett, Alice; Talukdar, Sabrina; Izatt, Louise; Brady, Angela F; Whyte, Sinead; Josephs, Katherine S; Shanmugasundaram, Monisha; Guillemot, Li Shan; Vakili, Dara; Ey, Shevaun; Ahmed, Munaza
Abstract : Background: The most common cancer diagnosed in germline TP53 pathogenic variant (PV) carriers is premenopausal breast cancer. An increased rate of breast tumour HER2 positivity has been reported in this group. Screening for breast/other cancers is recommended in PV carriers. Objectives: 1. To assess the frequency of germline TP53 PVs reported diagnostically in women with breast cancer at <30 years of age. 2. To evaluate the impact of personal/family history and HER2 status on the likelihood of germline TP53 pathogenic/likely pathogenic variant (PV/LPV) identification. Methods: Genetic test results from patients undergoing diagnostic germline TP53 tests between 2012 and 2017 in the four London Regional Clinical Genetics Services were reviewed. Clinical/pathology data and family history were extracted from genetics files for women diagnosed with breast cancer at <30 years. Results: The overall germline TP53 PV/LPV variant detection rate was 9/270=3.3% in all women diagnosed with breast cancer at <30 years and 2/171=1.2% in those with no second/subsequent cancer diagnosis or family history of TP53 -spectrum cancers. Breast cancers were significantly more likely to be HER2-positive in TP53 PV/LPV carriers than in non-carriers (p=0.00006). Conclusions: Germline TP53 PVs/LPVs are uncommon among women diagnosed with breast cancer aged <30 years without other relevant personal or family cancer history but have an important clinical impact when identified.